Lonicera caerulea L. polyphenols improve short-chain fatty acid levels by reshaping the microbial structure of fermented feces in vitro - Cao, Xinbo; Wang, Xuemeng; Ren, Yanxin; Sun, Yangcun; Yang, Zhichao; Ge, Jingping; Ping, Wenxiang (Frontiers in Microbiology, 2023)
Increasing evidence suggests that the pathogenesis of type 2 diabetes mellitus (T2DM) is closely related to the gut microbiota. Polyphenols have been shown to alleviate T2DM, but the effects of L. caerulea L. polyphenols (LPs) on the gut microbiota and metabolites remain elusive. In this study, the inhibitory effects of fermented L. caerulea L. polyphenols (FLPs) and unfermented L. caerulea L. polyphenols (ULPs) on α-amylase and α-glucosidase and the impact of LP on the gut microbiota and metabolites were investigated. Furthermore, the relationship between the two was revealed through correlation analysis. The results showed that ULP and FLP had the highest inhibitory rates against α-amylase and α-glucosidase at 4 mg mL -1 , indicating a strong inhibitory ability. In addition, LP plays a regulatory role in the concentration of short-chain fatty acids (SCFAs) and tends to restore them to their normal levels. LP reversed the dysbiosis of the gut microbiota caused by T2DM, as evidenced by an increase in the abundance of bacterial genera such as Lactobacillus, Blautia, and Bacteroides and a decrease in the abundance of bacterial genera such as Escherichia-Shigella and Streptococcus. Similarly, after LP intervention, the relationships among microbial species became more complex and interconnected. In addition, the correlation between the gut microbiota and metabolites was established through correlation analysis. These further findings clarify the mechanism of action of LP against T2DM and provide a new target for T2DM interventions.